2012
DOI: 10.1002/mds.25248
|View full text |Cite
|
Sign up to set email alerts
|

The glucocerobrosidase E326K variant predisposes to Parkinson's disease, but does not cause Gaucher's disease

Abstract: Background Heterozygous loss-of-function mutations in the acid beta-glucocerebrosidase (GBA1) gene, responsible for the recessive lysosomal storage disorder, Gaucher’s disease (GD), are the strongest known risk factor for Parkinson’s disease (PD). Our aim was to assess the contribution of GBA1 mutations in a series of early-onset PD. Methods One hundred and eighty-five PD patients (with an onset age of ≤50) and 283 age-matched controls were screened for GBA1 mutations by Sanger sequencing. Results We show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
102
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(113 citation statements)
references
References 28 publications
10
102
0
1
Order By: Relevance
“…The GBA p.E365K [p.E326K] mutation is considered a mild mutation as it has been demonstrated to reduce rather than abolish glucocerebrosidase enzyme activity (Alcalay, et al, 2015; Malini, et al, 2014). As such, homozygosity for this mutation is not sufficient to cause Gaucher disease; however, an increased frequency of heterozygous carriers has been demonstrated in cohorts of Parkinson disease supporting the notion that this mutation is pathogenic (Duran, et al, 2013; Nichols, et al, 2009). The GBA mutation p.R87Q [p.R48Q] has been previously described in a patient with Gaucher disease, but a role in parkinsonism for this particular rare mutation has not yet been reported (Rozenberg, et al, 2006).…”
Section: Resultsmentioning
confidence: 95%
“…The GBA p.E365K [p.E326K] mutation is considered a mild mutation as it has been demonstrated to reduce rather than abolish glucocerebrosidase enzyme activity (Alcalay, et al, 2015; Malini, et al, 2014). As such, homozygosity for this mutation is not sufficient to cause Gaucher disease; however, an increased frequency of heterozygous carriers has been demonstrated in cohorts of Parkinson disease supporting the notion that this mutation is pathogenic (Duran, et al, 2013; Nichols, et al, 2009). The GBA mutation p.R87Q [p.R48Q] has been previously described in a patient with Gaucher disease, but a role in parkinsonism for this particular rare mutation has not yet been reported (Rozenberg, et al, 2006).…”
Section: Resultsmentioning
confidence: 95%
“…Interestingly, more “severe” mutations (eg, 84GG or L444P) are associated with a higher risk for PD and with earlier PD onset when compared with “milder” mutations (eg, N370S) . GBA polymorphic variants (E326K, T369M) do not lead to GD but predispose to PD in most studies …”
Section: Discussionmentioning
confidence: 99%
“…A recent study has suggested that the GBA p.E326K variant could be the major driver of one of the GBA GWAS signals (Berge-Seidl et al 2017). Notably, this variant is not sufficient to cause Gaucher’s disease (Duran et al 2013) and it appears to have a lower odds ratio in PD compared to other Gaucher’s disease-linked mutations. Although this mutation on its own decreases glucocerebrosidase activity, residual activity is still better than other Gaucher’s disease mutations such as p.N370S and p.L444P (McNeill et al 2014).…”
Section: Common Risk Factors In Pdmentioning
confidence: 97%